Entre a Resistência e a Repressão: uma análise da Securitização dos Movimentos Sociais no Brasil e na Colômbia durante a Pandemia de COVID-19 - Bosco, Vander Finotti (2024)
The securitization process is a widely studied topic in international relations when we think about themes that address the international community and highlight the relationship between the speaker (securitizing agent) and the listener (Public Opinion). This work investigates the role of social media in the securitization of social movements during the COVID-19 pandemic, focusing on Brazil and Colombia. Based on Critical Security Studies and using Stritzel as a starting point for the analyses, it analyzes how States tend to frame social movements as threats to national security, associating them with terrorist acts. Using data triangulation, the research examines the impact of social media on the articulation and resistance of movements in the face of state repression, employing digital media analysis and field research to understand whether Stritzel's theory, previously examined from and for the Global North, can be used from the perspective of the Global South.